Analysis of Work Accident Prevention during the Loading and Unloading Process on MV. Tanto Nusantara at Tanjung Priok Port: Analisis Pencegahan Kecelakaan Kerja saat Bongkar Muat di KM. Tanto Nusantara pada Pelabuhan Tj. Priok - Nurmala, Eka; Laju, I Kadek; Dahlan, Harris R.; Muda, Indra; Syaputra, M. (PT. Alpha Trianguli Australis, 2025)
Occupational safety and health play a crucial role in the workplace, significantly impacting a company's productivity and success. Companies need to implement specific techniques and tools to foster a safe work environment that promote occupational health and safety. Many organizations now adopt the philosophy of